2007
DOI: 10.1001/archinte.167.16.1745
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesions and the Risk of Incident Hip Fracture in Older Persons<subtitle>Results From the Progetto Veneto Anziani Study</subtitle>

Abstract: Background: White matter lesions (WMLs) are associated with hypertension, an increased risk of falling, and impaired physical and cognitive performance that may affect the mechanical effect of falls. Methods: We hypothesized that WMLs are a risk factor for hip fracture (HF). We studied a sample of 820 community-dwelling Italian persons 65 years and older from the cohort of the Progetto Veneto Anziani Study who underwent brain magnetic resonance imaging at baseline. Subjects were classified as having no lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…However, those with increasing WMLV were more likely to have multiple falls, supporting a doseresponse relationship, and providing a potential explanation for the recent finding of an elevated fracture risk in those with severe WMLs. 29 Our findings parallel those from populationbased studies of WMLs and cognition in which the effects on cognition were seen predominantly in those with highest lesion loads. 22,28 The persistence of the association after exclusion of people with previous falls supports a temporal relationship between WML and incident falls.…”
Section: Discussionsupporting
confidence: 85%
“…However, those with increasing WMLV were more likely to have multiple falls, supporting a doseresponse relationship, and providing a potential explanation for the recent finding of an elevated fracture risk in those with severe WMLs. 29 Our findings parallel those from populationbased studies of WMLs and cognition in which the effects on cognition were seen predominantly in those with highest lesion loads. 22,28 The persistence of the association after exclusion of people with previous falls supports a temporal relationship between WML and incident falls.…”
Section: Discussionsupporting
confidence: 85%
“…Hip fractures were independently associated with diffuse WML in subjects less than 80 years, but this association was not detected in subjects older than 80 [23]. In contrast, our study does find an association between white matter pallor and falls in donors aged over 80.…”
Section: Discussioncontrasting
confidence: 96%
“…Total volume of white matter abnormalities seen on MRI has been associated with gait disturbance [5,[12][13][14][15][16][17][18], balance impairments [5, 13-15, 19, 20], increased tendency to fall [17,18,21,22] and hip fracture [23]. While some studies have demonstrated an association between decreased mobility and lesions located in deep white matter [24], others have found this more strongly associated with periventricular lesions [25,26], and a recent study suggested that both locations were independently associated with gait impairments and falls [27].…”
mentioning
confidence: 99%
“…16 According to the Leukoaraiosis and Disability in the Elderly study, patients with severe WMLs have impaired balance and typically have a history of twice as many falls when compared with mild WMLs. 7 In the study population of the present study, the rates of hip-fractures were even 4.0-fold in patients with moderate-to-severe WMLs when compared with patients with none-to-mild WMLs, whereas rates of trauma leading to hospital admission rates were 1.7-fold.…”
Section: Discussionmentioning
confidence: 99%
“…16 According to Cumulative risk of first hip-fracture after ischemic stroke in 383 patients of the Helsinki Stroke Aging Memory study cohort followed up for 12 years. Stratified for patients with none-to-mild and for moderate-to-severe white matter lesions (WMLs) on MRI.…”
Section: 배경과 목적mentioning
confidence: 99%